Impact of Hibiscus sabdariffa supplementation on human health: a narrative review - Szada-Borzyszkowski, Kacper; Owczarenko, Konstancja; Wróbel, Bartosz; Wójcik, Lena; Filipski, Michał; Gadzalski, Krzysztof (Journal of Education, Health and Sport, 2026)
Background. Hibiscus sabdariffa has been used for millennia in various medical traditions worldwide to treat a variety of illnesses. Due to this fact, scientists have analysed its potential medical properties, especially in most common diseases globally, such as hypertension, diabetes, or cancer, looking for a medicine that is effective, widely available, and inexpensive. Aim. The aim of this review is to summarize the current knowledge about Hibiscus sabdariffa supplementation on human health, with emphasis on the most common civilization diseases. Materials and methods. A narrative review of available literature in English language was conducted using PubMed, Scopus, and Google Scholar databases. Emphasis was placed on experimental studies, with clinical, placebo-controlled experiments prioritized. Conclusions. Hibiscus sabdariffa was found to have a positive impact on hypertension, hypercholesterolemia, obesity, renal and hepatic diseases. Moreover, the active compounds have anti-cancer properties, that could potentially help in developing new anti-cancer drugs in the future.